Orthogonal Array Testing Strategy (OATS) Payer Insurance Systems - Praveen Kumar Rawat (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The evolution of healthcare payer systems has led to an increase in complexity due to the diversity of health plans, service categories, provider types, authorization requirements, and member demographics. As a result, ensuring robust and cost-effective quality assurance has become a significant challenge. Traditional testing approaches often fall short when faced with the need to validate vast permutations of configurations and rules. To address this challenge, the Orthogonal Array Testing Strategy (OATS) emerges as a statistically grounded and highly efficient methodology for achieving extensive coverage with fewer test cases. OATS uses combinatorial mathematics to focus on pairwise or higher-order interactions among input variables, generating a representative set of test cases that ensure maximum defect detection with minimal redundancy. In the context of payer systems, this methodology enables accurate and scalable validation of mission-critical modules such as claims adjudication, benefit tier application, and eligibility verification. The use of orthogonal arrays drastically reduces the number of test scenarios while preserving thoroughness—making the testing process faster, more focused, and less resource-intensive. This approach is particularly advantageous for regulatory-sensitive systems, where compliance with CMS, HIPAA, and ACA mandates is mandatory. The structured methodology begins with identifying input variables and their values, followed by generating orthogonal arrays using tools such as ACTS or Hexawise. These test cases are then mapped to real-world payer scenarios and executed via automated test frameworks like Selenium and CI/CD tools such as Jenkins or GitLab CI. Post-execution, outcomes are analysed using dashboards and reporting platforms such as Allure or TestRail, with feedback loops feeding into continuous test improvement cycles. This enables early defect detection, traceable test coverage, and dynamic adaptability as systems evolve In conclusion, OATS offers healthcare payer organizations a robust and intelligent strategy for maintaining software quality, ensuring compliance, and reducing operational risk. It stands as an essential pillar of modern QA practice in healthcare IT, especially as payer systems continue to grow in complexity and interdependence. DOI: https://doi.org/10.17762/ijisae.v11i5s.7671